Frontopolar activity carries feature information of novel stimuli during unconscious reweighting of selective attention. (August 2022) - Güldener, Lasse; Jüllig, Antonia; Soto, David; Pollmann, Stefan
Abstract: Adapting to novelty is essential for an organism's survival in an uncertain world. Neuroimaging evidence consistently links the anterior prefrontal, specifically the frontopolar cortex (FPC; BA10), to exploratory reweighting of attentional weights thereby underscoring the role of the FPC in responding to environmental changes that are often complex and may occur very rapidly. Here we report new evidence showing that the FPC serves a role in attentional reallocation even in the absence of conscious awareness. Both mass-univariate and multivariate pattern analyses of fMRI data revealed that the right FPC and other attention-related areas not only are sensitive to unaware changes in the relevant stimulus dimension, but also that unconsciously processed information of the novel stimulus was globally represented across these regions. Our results indicate that unconsciously processed information can reach a global level of representation outside the occipitotemporal cortex, and that the FPC is crucial for the reweighting of selection biases in the absence of visual awareness.